Properties of Oryctes Baculovirus Isolated in Indonesia - Jun Kobayashi; Susamto Somowiyarjo (Jurnal Perlindungan Tanaman Indonesia, 1995)
An Indonesian isolate of Oryctes baculovirus was purified from infected midguts of the rhinoceros beetle (Oryctes rhinoceros) by centrifugation on a 10–40% (w/v) sucroese gradient. Morphological features of  nucleocapsid including a tail-like projection were very same as those previously reported. Both protein components of purified particles and restriction fragment electrophoresis profiles of viral DNA were similar to those of their isolates of Oryctes baculovirus, although there were some differences.